(untitled) (Agricultural Engineering, 2022)
This paper proposes a method to determine the optimal parameters for the drying of soybean using a kinematic vibration dryer. Among the main parameters of the investigated vibroconveyor are heat and mass transfer, physical and mechanical. The paper presents a mathematical model of the dependence of parameters of the soybean drying process of soybean built based on experimental data obtained by organizing an effective experiment plan with a sufficiently large number of factor levels. To determine the rational parameters for drying soybean, it is important to build the most accurate and adequate mathematical model, which will determine the most accurate values of the required parameters. For this purpose, it is recommended to conduct an experiment with as many levels of factors as possible. The article proposes an experiment established on a dedicated balanced orthogonal plan, which is optimal according to the D-efficiency criterion. Based on the experimental data, an adequate mathematical model of the dependence of the drying characteristics of soybean (moisture of the processed material (%), temperature inside the product layer (°С) on the parameters – vibration amplitude (mm), distance from the conveyor surface (mm), radiation power (Wt), weight (g·min−1). Following the analysis of the constructed mathematical model, optimal parameters of the developed vibroconveyor infrared dryer were substantiated. The main characteristics of the vibroconveryor mechanism of interoperational transportation of bulk products in the working area were also determined, and a technical and economic analysis of the developed oscillatory system was conducted.